Medicinal plants used against gynecological disorders by the local inhabitants of District Budgam, Kashmir Himalaya - Niyaz , Mohsina; Hussain Andrabi, Syed Aasif; Afzal Mir, Rayees (Ethnobotany Research and Applications, 2023)
Background: Medicinal plants are an essential part of the human health care system and are used to treat a variety of gynecological issues. Due to low living standards, famine, and strenuous physical labor, rural women frequently experience gynecological issues, even while pregnant. The objective of this study was to document the indigenous knowledge of local flora indigenous knowledge on the treatment of various gynecological disorders in the district Budgam, Jammu and Kashmir. Methods: To assess the medicinal plants’ utility in the region, a quantitative analysis including the Use value (UV) and Family use value (FUV) was carried out. Key informants were interviewed through semi-structured interviews, as well as group discussions. Results: A total of 51 medicinal plant species from 28 families are used to treat 33 distinct gynecological disorders. Among these families; Asteraceae was the dominant family (08 species).The leaves were the most commonly used part (34%). Herbs dominated all other life forms by (36 species).The most typical way to consume the medications was by decoction 39%, (32 species).According to the current study; the most prevalent disease addressed by the medicinal plants included is menstrual problems (36%). The Highest (UV of 0.65) were calculated for Artemisia absinthium while as the lowest (UV of 0.21) for Celtis australis. The highest family use value (FUV) was reported for Asparagaceae (0.50) while as the lowest FUV was calculated for Amaranthaceae (0.31). Locals continue to value herbal treatments as a trustworthy means of curing a variety of ailments. Conclusions: The current study demonstrates that rural women frequently experience gynecological problems and depend on traditional medical care. The result also indicates that the local population is sensitive and careful about gynecological diseases. This study is providing a baseline for future pharmacological studies to discover new herbal drugs to treat a variety of gynecological issues. Keywords: Traditional knowledge; Rural women; Ethnomedicine; Gynecological disorders; Kashmir Himalaya